EFFECTIVENESS OF THE RAPID RESPONSE UNIT PROGRAM OF THE MUNICIPAL POLICE IN CONTROLLING STREET VENDORS IN PALEMBANG CITY, SOUTH SUMATRA PROVINCE - Rahman, Hanif Aunur; Wahab, Abdul (Law Studies and Justice Journal (LAJU), 2026)
The persistence of street vendors (PKL) violating local regulations in public spaces remains a significant challenge in Palembang City, contributing to traffic congestion, public disorder, and disruption of urban spatial functions. This study aims to analyze the effectiveness of the Rapid Reaction Unit (URC) Program of the Palembang City Civil Service Police Unit (Satpol PP) in controlling street vendors using Richard M. Steers’ (1985) organizational effectiveness theory, which includes goal attainment, internal integration, adaptation to the environment, and stakeholder satisfaction. This qualitative descriptive study collected data through in-depth interviews with key informants (URC officers, street vendors, and community members), direct field observations, and documentation of Satpol PP activity reports and the SANG MASTER system data from 2021 to 2025. Data were analyzed using an interactive model involving data reduction, data display, and conclusion drawing, with validity ensured through source and method triangulation. The findings indicate that the effectiveness of the URC Program is categorized as fairly good. Goal attainment is relatively optimal in responding to public complaints and conducting routine patrols. However, obstacles persist in inter-agency integration that is not fully synergistic, situational adaptation, and limitations in human resources, facilities, infrastructure, and operational budget. Stakeholder satisfaction varies: the general public tends to support the program for improved orderliness, while street vendors express objection due to the lack of sustainable relocation and economic empowerment solutions. This study recommends strengthening human resource capacity, increasing operational budgets, and enhancing cross-sectoral synergy to make the URC Program more effective and sustainable in maintaining public order in Palembang City.